Implikasi Kecerdasan Emosional Terhadap Prestasi Kerja Dosen Sekolah Tinggi Maritim Yogyakarta (STIMARYO) - Suyanti Suyanti; Sahudiyono Sahudiyono (Majalah Ilmiah Bahari Jogja, 2020)
This study examines the implications of emotional intelligence on the work performance of Yogyakarta Maritime College (STIMARYO) lecturers. The problem under study is the influence of emotional intelligence factors on Yogyakarta Maritime College lecturers' work performance. This research is a quantitative study that uses primary data as a source of data. Data were obtained from distributing questionnaires to Yogyakarta Maritime College employees. Data were analyzed using simple linear regression. The results of the study concluded that there were positive and significant factors of intelligence on the work performance of Yogyakarta Maritime College lecturers. The existence of a positive influence is known from the positive regression coefficient 0.549. Significant differences were obtained from the results of the F test and t test which obtained a significance value of 0.004 (<0.05).